The effect of employee silence dimensions on affective commitment - Rizky Rahmatari Handayani; Haryadi Haryadi; Ratno Purnomo (Jurnal Akuntansi, Manajemen dan Ekonomi, 2017)
This research is a survey research at employees of KPP Pratama (Tax Service Office) Purwokerto branch. This study takes the title: "The Effect of Employee Silence Dimensions to Affective Commitment". The purpose of this study was to determine the effect of Employee Silence dimensions (in Indonesian silence means silence, silence, silence, silence, or silence) on employee affective commitment. The population in this study were employees of KPP Pratama (Tax Service Office) Purwokerto branch. The number of respondents taken in this study was 54 respondents, then purposive sampling method was used as a means of capturing respondents in accordance with this study.Based on the results of the study and data analysis using Multiple Regression Analysis shows that: (1) Acquiescent Silence has no significant effect on Affective Commitment, (2) Defensive Silence has a negative effect on Affective Commitment, (3) Diffident Silence has no significant effect on Affective Commitment, and (4) Deviant Silence negatively affects the Affective Commitment.The implication of the above conclusions is that it is better for Purwokerto Primary KPP employees to maintain a loyal attitude and willingness to share opinions or input to the organization as a form of participation in order to build a solid and solid organization. In the process, there is a need for positive enthusiasm and healthy competition among employees to strengthen family values as fellow members of the organization.